2019
DOI: 10.3390/condmat4010023
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the HOPG Intercalation Process

Abstract: Graphite intercalation via chemical strategies is a common procedure to delaminate stratified crystals and obtain a suspension of graphene flakes. The intercalation mechanism at the molecular level is still under investigation in view of enhancing graphene production and reducing damage to the original pristine crystal. The latter, in particular, can undergo surface detriment due to both blister evolution and carbon dissolution. The role of the electrolyte temperature in this process has never been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…HOPG is a high-quality stratified crystal, which allows a control of the electrochemical intercalation of anions. We have acquired data on the role played by the electrolytes [24], the temperature and the time effects [25,26], the electrolyte pHs [27], the structure [28] and the morphological [29] evolution of the HOPG electrode surface and paved the way to a first investigation of the buried graphite layers [30]. Finally, we succeeded in refining the current interpretation model of the involved chemical reaction [31].…”
Section: Introductionmentioning
confidence: 99%
“…HOPG is a high-quality stratified crystal, which allows a control of the electrochemical intercalation of anions. We have acquired data on the role played by the electrolytes [24], the temperature and the time effects [25,26], the electrolyte pHs [27], the structure [28] and the morphological [29] evolution of the HOPG electrode surface and paved the way to a first investigation of the buried graphite layers [30]. Finally, we succeeded in refining the current interpretation model of the involved chemical reaction [31].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the electrolyte temperature in this process has never been investigated. In work [17], by using an in situ atomic force microscopy (AFM) apparatus, the surface morphology changes after the application of fast cyclic-voltammetries at 343 K have been explored, in view of de-coupling the crystal swelling phenomenon from the other electrochemical processes. It was found that blisters do not evolve because of the increasing temperature, while the quality of the graphite surface becomes significantly worse, due to the formation of some adsorbates on possible defect sites of the electrode surface.…”
Section: Temperature Effects On the Hopg Intercalation Processmentioning
confidence: 99%
“…In these works, the local morphological changes occurring at the basal plane were observed. Recently, a new experimental effort successfully found the time scale of blistering evolution by means of EC-scanning tunneling microscopy (EC-STM), cyclic voltammetry (CV), and normal-pulse voltammetry (NPV). These results and the detailed analysis of the electrolyte characteristics (e.g., solution, pH, or temperature) show that the graphite basal plane swells as soon as the oxygen evolution potential (OEP) is reached, thus suggesting a first refinement of the current interpretative model. However, microscopic techniques are not really suitable when a more chemical analysis is required.…”
Section: Introductionmentioning
confidence: 99%